Efficacy of Wii-Fit on Static and Dynamic Balance in Community Dwelling Older Veterans: A Randomized Controlled Pilot Trial - Kalpana P. Padala; Prasad R. Padala; Shelly Y. Lensing; Richard A. Dennis; Melinda M. Bopp; Christopher M. Parkes; Mark K. Garrison; Patricia M. Dubbert; Paula K. Roberson; Dennis H. Sullivan (Journal of Aging Research)
Background/Objectives. Balance problems are well-established modifiable risk factors for falls, which are common in older adults. The objective of this study was to establish the efficacy of a Wii-Fit interactive video-game-led physical exercise program to improve balance in older Veterans. Methods. A prospective randomized controlled parallel-group trial was conducted at Veterans Affairs Medical Center. Thirty community dwelling Veterans aged 68 (±6.7) years were randomized to either the exercise or control groups. The exercise group performed Wii-Fit program while the control group performed a computer-based cognitive program for 45 minutes, three days per week for 8-weeks. The primary (Berg Balance Scale (BBS)) and secondary outcomes (fear of falling, physical activity enjoyment, and quality of life) were measured at baseline, 4 weeks, and 8 weeks. Results. Of 30 randomized subjects, 27 completed all aspects of the study protocol. There were no study-related adverse events. Intent-to-treat analysis showed a significantly greater improvement in BBS in the exercise group (6.0; 95% CI, 5.1–6.9) compared to the control group (0.5; 95% CI, −0.3–1.3) at 8 weeks (average intergroup difference (95% CI), 5.5 (4.3–6.7), p < 0.001) after adjusting for baseline. Conclusion. This study establishes that the Wii-Fit exercise program is efficacious in improving balance in community dwelling older Veterans. This trial is registered with ClinicalTrials.gov Identifier NCT02190045.